2009
DOI: 10.1080/09273940902741709
|View full text |Cite
|
Sign up to set email alerts
|

Ocular Syphilis—Back Again: Understanding Recent Increases in the Incidence of Ocular Syphilitic Disease

Abstract: Syphilis has reemerged in developed countries. This may be related to the post-AID S/HAART era, with a growing pool of HIV-positive men who oftenly practice unsafe sex. We underscore the importance of a high index of suspicion of ocular syphilis in patients with these characteristics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
27
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 57 publications
(30 citation statements)
references
References 19 publications
3
27
0
Order By: Relevance
“…All patients in this series were men, which is in agreement with other series on ocular syphilis demonstrating a predominance of men [4,6,11,[15][16][17]. Although an early report [20] suggests an increase in the number of cases of syphilis among women, most series on ocular syphilis, including ours, have not reflected this change.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…All patients in this series were men, which is in agreement with other series on ocular syphilis demonstrating a predominance of men [4,6,11,[15][16][17]. Although an early report [20] suggests an increase in the number of cases of syphilis among women, most series on ocular syphilis, including ours, have not reflected this change.…”
Section: Discussionsupporting
confidence: 90%
“…This is likely due to a progressive decline in AIDSrelated mortality, as other series [4,5,14] studied patients seen earlier (1986)(1987)(1988)(1989)(1990)(1991)(1992)(1993)(1994)(1995)(1996) than the current series. In contrast, Fonollosa et al [6] observed a 75% co-infection rate among 12 patients seen between 2005 and 2007, all of whom had iritis and vitritis. The high rate of HIV coinfection observed in our series underscores the importance of HIV testing in patients presenting with ocular syphilis.…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations